A simple remote sensing based information system for monitoring sites of conservation importance. Issue 1 (February 2016) - Szantoi, Zoltan; Brink, Andreas; Buchanan, Graeme; Bastin, Lucy; Lupi, Andrea; Simonetti, Dario; Mayaux, Philippe; Peedell, Stephen; Davy, James
Abstract: Monitoring is essential for conservation of sites, but capacity to undertake it in the field is often limited. Data collected by remote sensing has been identified as a partial solution to this problem, and is becoming a feasible option, since increasing quantities of satellite data in particular are becoming available to conservationists. When suitably classified, satellite imagery can be used to delineate land cover types such as forest, and to identify any changes over time. However, the conservation community lacks (a) a simple tool appropriate to the needs for monitoring change in all types of land cover (e.g. not just forest), and (b) an easily accessible information system which allows for simple land cover change analysis and data sharing to reduce duplication of effort. To meet these needs, we developed a web‐based information system which allows users to assess land cover dynamics in and around protected areas (or other sites of conservation importance) from multi‐temporal medium resolution satellite imagery. The system is based around an open access toolbox that pre‐processes and classifies Landsat‐type imagery, and then allows users to interactively verify the classification. These data are then open for others to utilize through the online information system. We first explain imagery processing and data accessibility features, and then demonstrate the toolbox and the value of user verification using a case study on Nakuru National Park, Kenya. Monitoring and detection of disturbances can support implementation of effective protection, assist the work of park managers and conservation scientists, and thus contribute to conservation planning, priority assessment and potentially to meeting monitoring needs for Aichi target 11. Abstract : Change detection results of the validated Nakuru National Park and its vicinity (20 km). The change maps for 1990–2000 and 2000–2010 show the original class which has changed during the particular period, whereas 1990–2010 shows the actual (new) land cover class for the year 2010.